Pelatihan Artificial Intelligence (AI) Berbasis Canva Sebagai Inovasi Digital Dalam Pembelajaran Sejarah di Era 5.0 Kepada Guru Sejarah di MAS AL-IKHLAS Kota Jambi: Penelitian - Satria, Fahri Maulana; Yusnitiraps, Audry Nia; Dermawan, Fito (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Artificial Intelligence (AI)-Based Canva Training as a digital innovation in history learning in the 5.0 era was conducted to enhance the digital competence of History teachers at MAS Al-Ikhlas, Jambi City. This program aimed to equip teachers with the skills to utilize AI technology and the Canva platform as interactive, creative, and student-centered learning media. The training methods included material presentation, hands-on practice, and mentoring in developing AI-based digital learning media. The results indicated an improvement in teachers’ ability to design engaging history content and integrate technological elements into their teaching process. This training serves as a strategic step toward transforming history learning into an innovative and future-oriented approach in the Society 5.0 era.